Methyl Viologen@β-Zeolite with Absorption/Fluorescence Dual-Mode and Photo/Chemical Synergistic Stimuli-Responsive Chromism - Han, Jingxuan; Li, Shaoning; Li, Huihui; Li, Yu; Qin, Jiaqiao; Wang, Fuxiang; Pan, Qinhe (Molecules (Basel, Switzerland), 2025)
In this work, methyl viologen (MV) was adsorbed into the nanopores of Si/Al H-β-zeolite via cation exchange. The resulting MV@β-zeolite possessed absorption/fluorescence dual-mode and photo/chemical synergistic stimuli-responsive chromism. Owing to the acidic surrounding provided by β-zeolite, the chromism of MV required the synergistic stimuli of UV irradiation and a chemical reductant (such as Na2SO3). UV irradiation induced single electron transfer from the chemical reductant to MV@β-zeolite, leading to enhanced absorption at 610 nm together with a daylight color change from pale yellow to blue. Meanwhile, the nanopores of β-zeolite inhibited aggregation-caused quenching of MV, enabling MV to emit cyan fluorescence at 500 nm. After the single electron transfer of the chemical reductant under UV irradiation, the cyan fluorescence of MV@β-zeolite was quenched. Additionally, MV@β-zeolite exhibited a short stimulus response time (250 s) and good color change reversibility. These findings in this work provide valuable insights into the design of multi-mode and synergistic stimuli-responsive viologen-based chromic materials, particularly for applications in secure high-throughput information storage, high-level anti-counterfeiting and multi-target multi-mode sensing.